147 ESTABLISHING A PERI-OPERATIVE MEDICAL SERVICE (POMS) FOR OLDER PEOPLE IN UROLOGY. (25th October 2022) - O'Donovan, C; Samida, S; Reynolds, S; Miller, P; Burrows, S
Abstract: Background: Older adults account for approximately 65% of patients undergoing urological procedures therefore as the population ages the demand is anticipated to rise. The benefits of Comprehensive Geriatric Assessment (CGA) have been proven in ortho-geriatrics and a number of surgical specialties but evidence in urology is lacking. The aim of this study was to assess the impact of a Peri-Operative Medical Service for older people (POMS) on patient outcomes in a urology inpatient population. Methods: This was a single-centre retrospective study of patients ≥50 years with length of stay (LOS) >1 day admitted over two four month periods in 2018 (Pre-intervention) and 2019 (Intervention). Group differences in LOS and complications were examined using univariate regressions and then adjusted for sex, emergency admission, severity of procedure and Charlson Co-morbidity Index which also accounts for age. Secondary outcomes were to record undiagnosed medical conditions identified and the interventions made by the POMS. Results: There were a total of 218 admissions from 211 patients with equal numbers of admissions in both the pre-intervention and intervention groups. No significant differences were detected for LOS (median 3 vs 4 days, p=0.11) or complications (32(29%) vs 40(37%), p=0.23) between pre-intervention and intervention groups. A new medical diagnosis was made in 13 (12%) of the pre-intervention v 43(39%) of the intervention group (p<0.001). The POMS recommended a change to management in 102 admissions (94%). The most common intervention was medication review: 64(59%) v 19(17%) (p<0.001). Conclusion: The Peri-Operative Medical Service for older people can improve patient management by identifying and managing medical issues, complications and geriatric syndromes that may otherwise have been missed.